Constituting law : legal argument and social values - Gleeson, Justin T.; Higgins, Ruth C. A. (Federation Press, 2011)
"Legal argument involves a search for reasons which resonate. These reasons are often derived from various sources other than domestic legal principles, sources which include history, morality, economics, philosophy, psychology, human rights discourse and international legal or commercial thought and practice." -- Source other than Library of Congress